Accountability Practices Of Waqf Institution In Malaysia: A Critical Analysis - Abdullah Mohamed Ahmed Ayedh; Aimi Fadzirul Kamarubahrin; Khairil Faizal Khairi (Mashhad: Behzad Hassannezhad Kashani, 2024)
Indexed by Scopus